Energy transfer, pre-reactive complex formation and recombination reactions during the collision of peroxy radicals. Issue 17 (13th April 2022) - Daub, Christopher David; Zakai, Itai; Valiev, Rashid; Salo, Vili-Taneli; Gerber, R. Benny; Kurtén, Theo
Abstract : Collisions between methyl peroxy radicals do not react in the triplet excited state, and lead to tetroxide formation in the singlet ground state. Abstract : In this paper we study collisions between polyatomic radicals – an important process in fields ranging from biology to combustion. Energy transfer, formation of intermediate complexes and recombination reactions are treated, with applications to peroxy radicals in atmospheric chemistry. Multi-reference perturbation theory, supplemented by coupled-cluster calculations, describes the potential energy surfaces with high accuracy, including the interaction of singlet and triplet spin states during radical recombination. Our multi-reference molecular dynamics (MD) trajectories on methyl peroxy radicals confirm the reaction mechanism postulated in earlier studies. Specifically, they show that if suitable pre-reactive complexes are formed, they will rapidly lead to the formation and subsequent decomposition of tetroxide intermediates. However, generating multi-reference MD trajectories is exceedingly computationally demanding, and we cannot adequately sample the whole conformational space. To answer this challenge, we promote the use of a novel simplified semi-empirical MD methodology. It assumes the collision is governed by two states, a singlet (S0 ) and a triplet (T1 ) state. The method predicts differences between collisions on S0 and T1 surfaces, and qualitatively includes not only pre-reactive complex formation, but also recombination processes such as tetroxide formation. Finally, classical MD simulations using force-fields for non-reactive collisions are employed to generate thousands of collision trajectories, to verify that the semi-empirical method is sampling collisions adequately, and to carry out preliminary investigations of larger systems. For systems with low activation energies, the experimental rate coefficient is surprisingly well reproduced by simply multiplying the gas-kinetic collision rate by the simulated probability for long-lived complex formation.